Registration of Guarantee Rights After The Issuance of The Minister of Agrarian Regulation And The Layout / Head of The National Land Agency Number 5 of 2020 Regarding Integrated Security Rights Services Electronically (Journal of Private and Commercial Law, 2021)
The publication of Ministerial Regulation No.5 of 2020 is a new step in the services provided by the Minister of The National Land to the community. Integrated electronic security services are based on Ministerial Regulation No. 5 of 2009 was carried out to adjust to the development of law, technology and the needs of society. Electronic mortgage services are new in Indonesia and need to be well understood by the users, in this case people who need fast, affordable, and easy mortgage services. This article is the result of a study that aims to analyze the implementation of security rights electronically. This research is a socio-legal research using primary and secondary data, also using qualitative analysis technique. The results of the research show that electronic mortgage services can run well even though there are some obstacles in the implementation. Electronic mortgage services are highly dependent on the web and internet facilities, so there is a need for a good network when operating this service. The quality of human resources needs to be improved in order to be able to face the era of the industrial revolution which all really depends on the technology.